Evaluation of Body Composition and Somatotype Characteristics of Male - Raphel3, V.A. Shafeeq1, George Abraham2*, Stalin (Journal of Experimental Sciences, 2010)
In an effort to describe the physique and body composition associated with performance of University level male track and field athlete of India, this study was conducted on 93 track and field athletes from South India, comprised of 22 sprinters (100 and 200 mts), mean age 19.5 years, height 172.1cm and weight 68.2 kg, 20 middle distance runners (800 and 1500 mts), mean age 19 years, height 166.8cm and weight 62.5 kg, 16 long distance runners (5000 and 10000 mts), mean age 18.7 years, height 167.2cm and weight 62.1kg, 20 throwers, (shot, discus and hammer throw), mean age 19 years, height 170.8cm and weight 72.6 kg and Jumpers (High, long and triple jump), mean age 18.3 years, height 169.9cm, weight 64.1kg. Besides height and weight, six skinfolds (triceps, chest, subscapular, abdomen, suprailiac and calf), two bicondylar breadths (humerus and femur) and two girths (biceps and calf) were measured. Somatotype evaluations were made according to Heath & Carter method. Percent body fat was assessed using equation prescribed by Berzerk et al. (1963). BMI was calculated as body mass divided by square of height (kg/m2). The somatochart indicated that sprinters and middle distance runners are ectomorphic mesomorphs, long distance runners are mesomorph ectomorphs while throwers are endomorphic mesomorphs. The jumpers fell into the somatotype category of balanced mesomorphs. Among all groups body fat percentage is lowest in sprinters (6.23±.83%) and highest in throwers (7.38±.85%). This was reflected in their endomorphic components which is lowest in sprinters (2.53±.0.45) and highest in throwers (3.39±0.65). Ectomorphic component is highly marked in long distance runners (3.56±0.65) while mesomophy was highest in sprinters (4.31±0.91). Throwers have significantly higher values of skinfolds than other groups. Compared to their overseas counterparts, the athletes of both track and field events in the present study exhibited greater endomorphic values. The present data will serve as a reference standard for the anthropometry and body composition of Indian track and field athletes.